Government's Strategy in Minimizing Violence Against Children In Lhokseumawe City - Ahmad Yani; Alwi Alwi; Ti Aisyah; Muryali Muryali (International Journal of Public Administration Studies, 2022)
The Government's Strategy in Minimizing Violence against Children in the Office of Women's Empowerment, Child Protection, Population Control, and Family Planning of Lhokseumawe City. The problem that occurs in this study is cases of violence against children that continue to occur every year, especially cases of child abuse (Aged 5-12 years) where in 2016 there were 5 cases, in 2017 it increased by 15 cases and then in 2018 it decreased by 4 cases then in 2019 (Second Quarter) increased to 5 cases,  so that reliable strategies from the government are needed to reduce cases of violence. The focus of this research is on how the strategy is carried out by the government and what are the obstacles faced when implementing the strategy. The purpose of this study is to find out how the strategy to minimize violence against children and what obstacles are faced by DP3AP2KB Lhokseumawe City.   This research uses a qualitative approach with a descriptive method. In collecting data, researchers make observations, interviews, and documentation. The results of the research that have been obtained by researchers explain that the strategy carried out in minimizing violence against children is to carry out prevention and handling efforts and in implementing the strategy experience obstacles, namely the allocation of the budget for child protection is still limited and the strengthening of human resources (HR) is still weak, causing the programs that have been planned to be still less than optimal,  and the lack of public awareness and knowledge to report/follow up on violence that occurs which causes perpetrators to experience less deterrent effects. With this problem, DP3AP2KB of Lhokseumawe City must continue to improve its performance optimally and thoroughly so that acts of violence against children do not occur again.